Openings : a memoir from the women's art movement, New York City 1970-1992 - Moore, Sabra (New Village Press, 2016)
"Memoir chronicling Sabra Moore's and other women artists' involvement in the feminist art movement and responses to racial tensions and reconciliation, war, struggles for reproductive freedom, and general social upheaval in New York City in the 1970s and 1980s"--